RANCANG BANGUN E-COMMERCE PADA TOKO KERUDUNG NURI COLLECTION BERBASIS CUSTOMER RELATIONSHIP MANAGEMENT - Linda Durotul Ummah (NUANSA INFORMATIKA, 2018)
E-commerce is a contact of trade transactions between seller and buyer by using electronic media. The advantage gained by using transactions through e-commerce is to increase revenue by using online sales that cost less. E-commerce on Nuri Collection's shop based veil Customer Relationship Management (CRM), namely the application of Customer Relationship Management (CRM) is not directly said as a computerized data customer. It is intended that the company knows what the needs and wants of customers so that it can establish a good relationship with customers. The purpose of this research is to know consumer opinion about Customer Relationship Management (CRM) which conducted by company, analyze consumer loyalty to Nuri Collection product. E-commerce is built using Waterfall system development method, with a system design tools such as Flowmap, DFD, Context diagram, ERD. While in making this e-commerce writer use programming language PHP and MYSQL as database.Keywords: E-commerce, CRM, PHP